Numerical analysis and simulation of unitary air conditioning system using heat exchanger with hydrocarbon refrigerant - Nuriyadi, Muhammad (International Conference on Industrial Revolution for Polytechnic Education, 2021)
The environmental issues to be addressed, particularly in refrigeration and air conditioning, is the destruction of ozone layer and the effects of global warming due to the usage of un-environmental friendly refrigerant, as R22, or generally synthetic refrigerant. These refrigerants had high ODP and GWP. One alternative refrigerant is hydrocarbon refrigerant (HC). Hydrocarbons have several advantages such as environmental friendly and replace the previous refrigerant, without replacing components, and less filling need. The working pressure is also lower, thus reducing the power consumption. With these advantages, the Hydrocarbon refrigerants are good alternative. In other hand, to improve performance of refrigeration system is by lowering the temperature of liquid line using heat exchanger. In this study, numerical simulation was conducted to examine the effect of liquid to suction heat exchanger utilization on the performance of a unitary air-conditioning system using hydrocarbon refrigerant as a cooling fluid. The results are, heat exchanger utilization increases refrigeration effect by rising of effectivity, the highest increasing is about 7%. LSHX also rise up the compression work with increase of effectivity by 19%. Coefficient of performance (COP) and relative capacity index decrease by 5%. Decreasing of performance is higher in the unit that operates at higher temperature.